Decomposition of Postseismic Signals Following ≥Mw 6 Earthquakes on Sumatra Island Based on Sumatran GPS Array (SuGAr) Observations - Tattyana Wening Kalbuadi; Nurrohmat Widjajanti; Cecep Pratama (Universitas Gadjah Mada, 2026)
Indonesia, located at the convergence of four major tectonic plates, experiences frequent large earthquakes, particularly in Sumatra, due to the subduction of the Indo-Australian Plate and the Sumatra Fault Zone (SFZ). While most postseismic studies focus on events with magnitudes ≥7 Mw, this research investigates earthquakes with magnitudes ≥6 Mw to characterize postseismic deformation on Sumatra Island. Using SuGAr GPS time series data from 2002 to 2023, postseismic signals were decomposed and modelled using an exponential decay function to isolate transient deformation and estimate decay time parameters. Model performance was evaluated through RMSE comparisons and two-parameter significance tests at the 95% confidence level. The results indicate consistent RMSE patterns in the NS and EW components, whereas the UD component shows greater variability, suggesting that the model effectively captures horizontal postseismic motion but is less sensitive to vertical displacement.